Aluminosilicate haloes preserve complex life approximately 800 million years ago. Issue 4 (12th June 2020) - Anderson, Ross P.; Tosca, Nicholas J.; Cinque, Gianfelice; Frogley, Mark D.; Lekkas, Ioannis; Akey, Austin; Hughes, Gareth M.; Bergmann, Kristin D.; Knoll, Andrew H.; Briggs, Derek E. G.
Abstract : Mudstone-hosted microfossils are a major component of the Proterozoic fossil record, particularly dominating the record of early eukaryotic life. Early organisms possessed no biomineralized parts to resist decay and controls on their fossilization in mudstones are poorly understood. Consequently, the Proterozoic fossil record is compromised—we do not know whether changing temporal/spatial patterns of microfossil occurrences reflect evolution or the distribution of favourable fossilization conditions. We investigated fossilization within the approximately 1000 Ma Lakhanda Group (Russia) and the approximately 800 Ma Svanbergfjellet and Wynniatt formations (Svalbard and Arctic Canada). Vertical sections of microfossils and surrounding matrices were extracted from thin sections by focused ion beam milling. Elemental mapping and synchrotron-based infrared microspectroscopy revealed that microfossils are surrounded by haloes rich in aluminium, probably hosted in kaolinite. Kaolinite has been implicated in Cambrian Burgess Shale-type (BST) fossilization and is known to slow the growth of degraders. The Neoproterozoic mudstone microfossil record may be biased to tropical settings conducive to kaolinite formation. These deposits lack metazoan fossils even though they share fossilization conditions with younger BST deposits that are capable of preserving non-mineralizing metazoans. Thus metazoans, at least those typically preserved in BST deposits, were probably absent from sedimentary environments before approximately 800 Ma.